Regional Variation and Determinants of Well-being of the Elderly in India - Das, Bhaswati; Sengupta, Rituparna; Paul, Kalosona (Journal of Population and Social Studies [JPSS], 2018)
The paper assessed the level of well-being in six states in India, namely Himachal Pradesh, Punjab, West Bengal, Odisha, Kerala, Tamil Nadu and Maharashtra. The index of well-being was developed based on the Stanford Centre on Longevity (SCL) Index of well-being, Global ageing and Monitoring Project, 2011 with certain modifications. Indices for physical, social and emotional well-being are constructed using data from the Building a Knowledge Base on Population Ageing in India (BKPAI), Sample Registration System, Census of India and National Crime Records Bureau. The indices were thereafter combined to form the well-being index. Marital status, educational level, employment status, annual income, health status and regional factors emerged as strong determinants of elderly well-being through a multinomial logistic regression. The states varied in rank in the components of well-being revealing paradoxes. The differentials in different domains need to be emphasized in the state specific policy for the aged.